VALIDITAS TAFSÎR BI AL-‘ILMÎ DALAM PENAFSIRAN AYAT-AYAT PENCIPTAAN ALAM - Theo Jaka Prakoso (Jurnal Studi Ilmu-ilmu Al-Qur'an dan Hadis, 2020)
Progress of knowledge provides a major influence on the development of other knowledge, including in the field of Quranic interpretation. The achievements of modern science provide a new color in the method of interpreting the Qur'an. The tendency of interpreters using the progress of science gave birth to the method of tafsir bi al-‘Ilm (scientific interpretation). As a new method, tafsir bi al-‘Ilmi becomes one of the methods which is validated. Although some people use this method as a proof of Qur'anic miracles, this study aims to find out the validity of the truth of tafsir bi al-'Ilmi by using the theory of truth in the philosophy of science. This study uses a text analysis method to provide an understanding of the views that use the method of tafsir bi al-'Ilmi as a way to understand the Quran. This study found that the use of scientific discoveries as an approach to prove that the Qur'an contains explanations for natural phenomena is carried out by some modern interpreters, such as Tantawi Jawhari, Sayyid Qutb and M. Quraish Shihab. They assume that al-Dhariyat (51): 47, al-Anbiya (21): 30, Fussilat (41): 11, Hud (11): 7 and al-Haj (22): 47 explain the creation of nature in accordance with the discoveries of modern science. However, in this study, the interpretation of these verses by using the theory of correspondence, the theory of coherence, and consensus theory were not found to be true. Therefore, this study supports the opinions of al-Shatibi, al-Dhahabi, and Muhammad Shaltut, who rejected the validity of tafsir bi al-'Ilmi.